Efektifitas Model Pembelajaran Discovery Learning Terhadap Peningkatan Hasil Belajar Siswa SMA Negeri 2 Ternate Pada Materi Suhu dan Kalor - Endang Fitria (Jurnal Ilmiah Wahana Pendidikan, 2023)
A discovery learning model is used, in which this model focuses on independent information seeking and information processing for organizational purposes. The purpose of this study was to determine the effectiveness of the discovery learning model in improving students' cognitive learning outcomes in terms of motion and speed material. This study used a quantitative pretest design approach using the One Group-Pretest-Posttest method. The sampling technique used purposive sampling with a sample of 36 students. Data collection with testing techniques. The data analysis technique is the N-armature test. The results of this study indicate that students' cognitive learning outcomes increased during the period of applying the N-gain learning model in the middle class with 19 students and the percentage was 59.65 in the high class with 17 students. with a percentage of 40.35%. In addition, there are significant differences in students' cognitive learning outcomes before and after the application of the discovery learning model. Based on the results of data analysis, the discovery learning model is effective in improving students' cognitive learning outcomes.